Dynamic evolvement of the de Winter ECG pattern - Jian Wang; ShuLing Diao; Baoxin Ma (Annals of Noninvasive Electrocardiology, 2021)
Abstract The de Winter electrocardiograph (ECG) pattern in patients with chest pain is associated with occlusion of the proximal left anterior descending (LAD) artery. These patterns were once considered stable conditions, without dynamic evolution of ECG. Recently, several case reports have indicated that this ECG pattern may evolve into ST‐elevation myocardial infarction (STEMI) or may follow the ECG manifestations of STEMI. However, our case report reveals a dynamic evolution from the de Winter pattern to STEMI and then to a normal ECG pattern.